Pengaruh Corporate Social Responsibility dan Struktur Kepemilikan terhadap Profitabilitas - Helen Carolyn; Achmad Fauzi; Tri Hesti Utaminingtyas (Yayasan Education and Social Center, 2023)
The purpose of this study is to determine the effect of Corporate Social Responsibility (CSR) and Ownership Structure proxied by Institutional Ownership on the profitability (ROA) of banks listed on the Indonesia Stock Exchange (IDX) for the period 2018-2020. The data used in this study are secondary data which are the annual reports of banks obtained from the bank's official website and the Indonesia Stock Exchange (IDX). The data used in this study is panel data, a combination of time-series and cross-sectional data, which is then processed using E-views 9 with multiple regression methods. The population is all banks listed on the Indonesia Stock Exchange (IDX) from the 2018-2020 period, totalling 47 banks and using purposive sampling, there are 39 banks as the final sample. The study's results stated that Corporate Social Responsibility (CSR) negatively affects ROA and Institutional Ownership has no effect on ROA. Through the F test conducted, the two independent variables (CSR and Institutional Ownership) are stated simultaneously affect ROA with a coefficient level determination of 77.18%.